Case report: Peptic ulcer disease in a professional athlete - Kim, P. K.; Dorshimer, G. W. (The Physician and Sportsmedicine, 2009)
Abstract: Peptic ulcer disease (PUD) is a common problem that affects 4 million people in the United States. Although its prevalence has not been studied in the athletic population, one would suspect PUD would affect athletes at a similar rate or higher based on the predispositions to certain risk factors of this disease. This case report addresses the particular predispositions for PUD in a professional football athlete.